2022
DOI: 10.3390/biomedicines10102405
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Performance of Novel Immunoassays for the Sensitive Quantification of Soluble PD-1, PD-L1 and PD-L2 in Blood

Abstract: Programmed death-1 receptor PD-1(CD279) and its corresponding ligands PD-L1(CD274, B7-H1) and PD-L2(CD273, B7-DC) play important roles in physiological immune tolerance and for immune escape in cancer disease. Hence, the establishment and analytical validation of a novel enzyme-linked immunosorbent assay (ELISA) to measure soluble PD-1, PD-L1 and PD-L2 in blood samples according to high quality standards is required. Antibody pairs were used to establish novel highly sensitive ELISAs for all three markers on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Our results are consistent with several studies in healthy subjects showing levels of different markers including IL-8, sPD-L1, and MIP-1β higher in serum than plasma. [21][22][23] These differences between the two matrices were not surprising considering previous evidence that different levels of some cytokines can be found between serum and plasma samples collected from the same subjects at the same time. [24][25][26][27] Serum preparation includes the formation of a cross-linked fibrin clot, which causes removal of circulating proteins (e.g., fibrinogen, prothrombin, thrombin, and coagulation factors).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our results are consistent with several studies in healthy subjects showing levels of different markers including IL-8, sPD-L1, and MIP-1β higher in serum than plasma. [21][22][23] These differences between the two matrices were not surprising considering previous evidence that different levels of some cytokines can be found between serum and plasma samples collected from the same subjects at the same time. [24][25][26][27] Serum preparation includes the formation of a cross-linked fibrin clot, which causes removal of circulating proteins (e.g., fibrinogen, prothrombin, thrombin, and coagulation factors).…”
Section: Discussionmentioning
confidence: 61%
“…Our results are consistent with several studies in healthy subjects showing levels of different markers including IL-8, sPD-L1, and MIP-1β higher in serum than plasma. 2123…”
Section: Discussionmentioning
confidence: 99%
“…Soluble PD-1, PD-L1, and PD-L2 in plasma can be measured by enzyme-linked immunosorbent assay (ELISA) [ 62 ]. Intra-assay imprecision measurements showed that the coefficient of variation did not exceed 10% for all three assays, while other analyses estimated good dilution linearity and selectivity of this method.…”
Section: Solutions To Enhance the Viability Of Pd-l1 Assessment Prior...mentioning
confidence: 99%
“…Currently, immunohistochemistry (IHC) methods based on anti-PD-L1 antibodies are mostly applied; however, they show inconsistent results depending on the specificity of the antibodies used. Recently, blood-based immunoassays were developed to sensitively detect and quantify soluble forms of PD-1, PD-L1, and PD-L2 [ 10 ]. This approach offers the advantage of quick, inexpensive, robust, and quantitative measurements in easily accessible patient blood that can be used to improve future oncoimmunology research as well as for the individual serial monitoring of the response to immune therapies in cancer patients [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides a thorough analytical validation [ 10 ], preanalytical handling conditions must be specified and standardized before the assays can be applied in clinical studies. It is well known that some protein profiles are affected by a variety of influencing factors occurring during collection and sample preparation processes [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%